Single-centre experience of refractory rheumatoid arthritis. Issue 2 (1st August 2022) - Fitton, John; Melville, Andrew; Naraghi, Kamran; Nam, Jacqueline; Dass, Shouvik; Emery, Paul; Buch, Maya H
Abstract: Objectives: The aim was to evaluate the proportion of RA patients who are refractory to multiple targeted therapies (TTs) in a real-world cohort of patients in a tertiary rheumatology referral centre, to describe patterns of drug sequencing associated with the development of refractory RA (RefRA) and to identify whether there is a subgroup of RefRA patients in whom successive drugs have shown primary lack of efficacy. Methods: Patients at a single centre were defined as refractory if they had failed two or more classes of TT and were identified from a dedicated TT clinic database. Reasons for drug failure were recorded, and patients were categorized pragmatically as having mild [failure of two biologic DMARD (bDMARD) classes], moderate [failure of at least three bDMARD classes] or severe [failure of at least two bDMARD classes and JAK inhibitor] refractory disease. Results: One hundred and seventy-two patients were identified as RefRA (>10% of our TT-exposed cohort); median [interquartile range (IQR)] TT exposures of four (two), 81.5% female, 82% seropositive, mean (s .d .) age of 63 (12.3) years. Detailed analysis of 60 patients showed a median (IQR) disease duration of 22 (10.75) years, median (IQR) time from diagnosis to initiation of first TT of 5 (10) years, and mean (s .d .) baseline DAS28CRP before starting first-line TT of 5.91 (0.84). Among RefRA patients, 15% were severely refractory, and 6% had demonstrated no clinical response to any TT. Conclusion: A small proportion of patients have true RefRA. Most patients fail multiple therapies owing to a combination of inefficacy and adverse events. Lay Summary: What does this mean for patients? Over the last 20 years, advanced drugs that target inflammation in RA have revolutionized treatment. However, a growing group of patients who have not responded to multiple targeted drugs has emerged. These patients have refractory RA. Rheumatologists can find refractory RA hard to manage, and the proportion of RA patients with refractory disease is unclear. We evaluated the number of patients with refractory disease within the RA population of a large hospital. We also described patterns in the sequence of drugs given to patients, because this can be associated with the development of refractory RA. We wanted to determine the different combinations of non-response to drugs, loss of response or drug side effects that led to refractory disease. We identified a small subgroup of patients who had no response to any of their treatments. These patients have true refractory RA. Future work investigating this subgroup of patients might help to shed light on how refractory RA develops.